Pemanfaatan Batu Gunung Limbong Kecamatan Rantepao Dalam Campuran Stone Matrix Asphalt Kasar - Chelia Febriyani Timbonga; Alpius; Louise Elizabeth Radjawane (Paulus Civil Engineering Journal, 2021)
In this study, using the aggregate from the Mount Limbong stone for a mixture of coarse Stone Matrix Asphalt. The research objective was to determine the aggregate characteristics and composition of the crude SMA. The results showed that the characteristics of the pavement material in the form of Limbong mountain rock, Rantepao District, met the specifications as a road pavement coating material. Through the conventional Marshall test, the characteristics of the mixture of rough Stone Matrix Asphalt (SMA) mixture with asphalt content are 6.00%, 6.25%, 6.50%, 6.75%, and 7.00%. Marshall Immersion test results obtained Remaining Marshall Stability of 94.16% with asphalt content of 7.00% fulfilling the requirements, namely> 90% in accordance with the General Specifications of Bina Marga 2018.